Quantitative analysis of left ventricular dyssynchrony using cardiac computed tomography versus three-dimensional echocardiography - Buß, Sebastian Johannes; Schulz, Felix; Wolf, David Gregor; Hosch, Waldemar P.; Giannitsis, Evangelos; Kauczor, Hans-Ulrich; Zugck, Christian; Becker, Rüdiger; Hardt, Stefan; Katus, Hugo; Korosoglou, Grigorios (European radiology, 2012)
Objectives We investigated whether cardiac computed tomography (CCT) can determine intraventricular dyssynchrony in comparison to real-time three-dimensional echocardiography (RT3DE) in patients who are considered for cardiac resynchronisation therapy (CRT).